1988
DOI: 10.1073/pnas.85.23.8978
|View full text |Cite
|
Sign up to set email alerts
|

Purified secB protein of Escherichia coli retards folding and promotes membrane translocation of the maltose-binding protein in vitro.

Abstract: The efficient export of a subset ofEscherichia coli envelope proteins is dependent upon the product of the secB gene. Previous studies indicated that SecB promotes the export of the periplasmic maltose-binding protein (MBP) by preventing premature folding of the precursor MBP in the cytoplasm into an export-incompetent form. In this study, SecB has been purified to homogeneity and shown to be a soluble, cytoplasmic, multimeric protein composed of identical 17-kDa subunits. SecB was required for efficient in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
169
1
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(173 citation statements)
references
References 24 publications
2
169
1
1
Order By: Relevance
“…SecB was purified from strain BL21(DE3) pJW25 (6). SecBL75Q, SecBE77K, and SecBF74I were purified from strain CK2212 (BL21 (DE3) secB::Tn5 srl::Tn10 recA) containing two plasmids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SecB was purified from strain BL21(DE3) pJW25 (6). SecBL75Q, SecBE77K, and SecBF74I were purified from strain CK2212 (BL21 (DE3) secB::Tn5 srl::Tn10 recA) containing two plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…Lysates-Soluble lysates were prepared (as above except that the growth temperature was 35°C) from the following strains: CK1953 (10), which carries the secB::Tn5 mutation and is secBnull; BL21(DE3) pJW25 (6), which carries the wild-type secB on the chromosome as well as on the plasmid; and CK2212 with two plasmids both containing either secBC76Y or secBV78F. One of the two plasmids carries the secB variant gene under its natural promoter, and the other plasmid carries the secB variant gene under control of the T7 promoter.…”
Section: Interaction Of Secb and Secb Variant Proteins With Precursormentioning
confidence: 99%
“…The initial evidence that SecB is oligomeric came from analysis by size-exclusion chromatography and electrophoresis of the native protein through polyacrylamide gels. However, a range of molecular weights have been reported: 64 kDa (Watanabe & Blobel, 1989), 79 kDa (Weiss et al, 1988), 90 kDa , and 115 kDa (Weiss et al, 1988), and thus the oligomeric state has not been determined definitively. The range of values obtained would be explained if SecB deviated from the ideal spherical structure because the techniques used base the determination of molecular weight on the separation of molecules according to their radii of gyration.…”
mentioning
confidence: 99%
“…SecB is one of the cytosolic factors which is required for the translocation of a subset of precursor proteins (Kumamoto and Beckwith, 1985). In-vitro studies with SecB purified from an over-producing (Weiss et al, 1988;Kumamoto et al, 1989) or non-over-producing (Watanabe and Blobel, 1989a) strain, showed that it promotes in a tetrameric (Watanabe and Blobel, 1989a) or an oligomeric (Weiss et al, 1988) form the translocation of in-vitrosynthesized precursor proteins. It has also been shown that SecB stabilizes the translocation-competent state of the purified precursors of the E. coli outer membrane proteins PhoE (prePhoE) and OmpA (preOmpA) diluted from concentrated urea solutions in vitro (Kusters et al, 1989; Lecker et al., 1989).…”
mentioning
confidence: 99%